Systemic Decoupling in Digital Foreigner Reporting: Uneven APOA Adoption in Surakarta - ⁠Fitriana Riscadewi Warisno; Sudarmo; Sri Yuliani (Administratio, 2026)
Indonesia has a legally supported digital mandate for reporting foreigners, but data intake in Surakarta’s accommodation sector remains minimal. This article aims to explain this gap by analyzing Aplikasi Pelaporan Orang Asing (APOA) as a digital governance arrangement rather than a fully realized surveillance system. The study uses a qualitative case study based on documentary analysis and secondary institutional data, covering immigration regulations, official APOA procedures, a Surakarta accommodation dataset, and relevant literature on digital governance, technology adoption, and migration control. The empirical snapshot shows a marked decoupling between digital policy and reporting reality: registration rose from 26 of 976 accommodation units on 2 September 2025 to 31 of 976 on 27 November 2025, or 3.18% overall coverage. Hotel coverage reached 8.89%, while non-hotel accommodation coverage remained 0.45%. These figures do not demonstrate causal explanations or comparative patterns across jurisdictions, but they show that APOA’s monitoring capacity is largely unrealized in this case. The article concludes that the central issue is a governance gap between formal control and actual compliance infrastructure: legal authority and platform availability are present, but coordination, reciprocal incentives, organizational follow-up, and trust-building remain insufficiently institutionalized.